2022
DOI: 10.1002/hbm.26078
|View full text |Cite
|
Sign up to set email alerts
|

Comparing adaptive coding of reward in bipolar I disorder and schizophrenia

Abstract: BackgroundDeficits in neural processing of reward have been described in both bipolar disorder (BD) and schizophrenia (SZ), but it remains unclear to what extent these deficits are caused by similar mechanisms. Efficient reward processing relies on adaptive coding which allows representing large input spans by limited neuronal encoding ranges. Deficits in adaptive coding of reward have previously been observed across the SZ spectrum and correlated with total symptom severity. In the present work we sought to e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Previous studies reported impaired OV adaptation in SCZ patients at the behavioral and the neural levels ( Kaliuzhna et al, 2023 ; Kirschner et al, 2016 , Kirschner et al, 2018 ; Wang et al, 2021 ). However, little research has been conducted to examine EV adaptation in SCZ patients.…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies reported impaired OV adaptation in SCZ patients at the behavioral and the neural levels ( Kaliuzhna et al, 2023 ; Kirschner et al, 2016 , Kirschner et al, 2018 ; Wang et al, 2021 ). However, little research has been conducted to examine EV adaptation in SCZ patients.…”
Section: Introductionmentioning
confidence: 89%